Portal corporativo como ferramenta de gestão do conhecimento - Reis, Maria Elisa Andries dos (2005)
The whole economic, political, social and cultural pattern of the world is assuming a different shape through an intensive usage of information and communication technology. In the global emerging societies, proactive management of knowledge has become quintessential for the very survival of any organization. The main focus is no longer on the storage and access to information, but instead on its strategic management and its innovative use by removing distances and cutting down steps of the productive process. This dissertation aims at pointing out the technolgical resources of information and communication which are better fit for a Corporate Portal environment, so as to add up to the actions related to Knowledge Management in public organizations. We sought to demonstrate that Knowledge Management associated to a Corporate Portal can be an essencial tool for the arrangement of an environment designed to share different knowledges and decision making which seeks innovation inside public organizations and more efficiency in serving the community.